Carbon nanotubes cement composites - Simone Musso; Jean-Marc Tulliani; Giuseppe Ferro (Fracture and Structural Integrity)
The present paper reviews the current state of the art of carbon nanotubes cement-based composites and the possible applications. The influence of carbon nanotubes additions onto cement paste mechanical and electrical properties are discussed in detail. Though promising, several challenges have still to be solved before the introduction of these new materials into the public sphere through civil infrastructures.